Endovascular repair of a life-threatening radiation-induced ruptured false aneurysm of the intrathoracic left subclavian artery: case report - Hizette P; Horn D; Lemaitre J; Segers B (Vascular Health and Risk Management, 2015)
Pascale Hizette, David Horn, Jean Lemaitre, Bernard SegersDepartment of Vascular and Thoracic Surgery, St Pierre University Hospital, Brussels, BelgiumAbstract: Massive hemorrhage in tracheostomy patients is generally described as a result of a tracheoinnominate artery fistula. Other etiologies for rupture of a false aneurysm are rare. The classical procedure for subclavian artery aneurysm is open surgery. Endovascular techniques have been accepted by several authors as a possible minimally invasive alternative. We report a life-threatening radiation-induced ruptured false aneurysm of the intrathoracic subclavian artery successfully treated by endovascular stent graft through left brachial access in a tracheostomy patient. Keywords: tracheostomy hemorrhage, radiation-induced aneurysm, subclavian artery, ruptured aneurysm, endovascular repair